Kesehatan Mental pada Remaja Muslim: A Systematic Review - Hasniaty, Hasniaty; Ashriady, Ashriady (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2026)
Adolescent mental health in Indonesia is a serious issue, with a high prevalence of disorders such as depression and anxiety. Social, academic, and family-related stress, as well as the influence of social media, have been shown to affect adolescents’ well-being. In the context of Muslim adolescents, Islam has significant potential to support psychological well-being, although studies examining the relationship between the two in Indonesia remain limited. This study aims to identify factors influencing the mental health of Muslim adolescents, assess the role of Islam in shaping mental health, and provide recommendations for faith-based interventions. The method used is a systematic review based on PRISMA guidelines, with literature searches conducted through Google Scholar, PubMed, Science Direct, and Scopus. The search covered publications from 2020 to 2025, resulting in an initial 615 articles. Inclusion criteria included original articles written in Indonesian or English and open access, while exclusion criteria covered review articles, systematic reviews, meta-analyses, and inactive DOIs. The findings indicate that social stress, academic demands, and family problems significantly contribute to the decline in Muslim adolescents’ mental health. Religious practices such as prayer, reading the Qur’an, and dhikr have been proven to support mental resilience and psychological well-being. Religious education and self-control also serve as important protective factors. It is recommended that programs to improve the mental health of Muslim adolescents involve collaboration between schools, families, and religious communities, provide safe spaces for sharing concerns, and utilize technology positively to reinforce religious values.